PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KEMAMPUAN BERMAIN PIANIKA SISWA KELAS IV SDN 05 PEKANBARU - Ventika, Yola Tesha; Antosa, Zariul; ', Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of this research is the low student in playing pianika fourth grade students of SDN 05 Pekanbaru. The purpose of this study is to improve learning outcomes Arts Culture and Skills fourth grade students of SDN 05 Pekanbaru to implement cooperative learning model. This study took place in SDN 05 Pekanbaru. This research is a classroom action research (PTK). The research subject is the fourth grade students of SDN 05 Pekanbaru with a total of 30 students. Based on the results, it can be concluded that the implementation of cooperative learning model can improve learning outcomes Arts Culture and Skills fourth grade students of SDN 05 Pekanbaru. It is known from learning outcome Cultural Art and Craft in each cycle. Increased activity of teachers at each meeting, the first meeting of the first cycleto the second cycle of meeting 2. In the first cycle only one student scored very high with a value of 91.7 (very high), 17 students who obtained high marks to the value of at least 75 (high), 12 students who obtained value with the value being 66.7 (moderate), and no students who received low ratings. The ability of the students in the second cycle increased at a very high and high ratings. Students who earn a very high score there are 5 students with a value of 91.7 (very high) and 25 students scored high with a value of 75-83.3 (high), while the medium and low values seen no student who obtained moderate and low ratings. Thus, the hypothesis if implemented cooperative learning model, it can improve students' skills in playing pianika fourth grade students of SDN 05 Pekanbaru, unacceptable.Keywords : cooperative learning model, students' skills in playing pianika